IT Governance Audit with COBIT 5 Framework on DSS Domain - Vernando Jarsa; Kevin Christianto (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Information technology in organizations plays an important role for the continuity of their current business processes. Almost every organization already has information technology and dependence on their information technology. With the existence of information technology, it can help business process in the organization runs smoothly, and according to desired by every organization. But not infrequently the information technology that has been operating has problems that are very annoying and hinder the business process of the organization. Problems that exist in this company is at the time of maintenance and custom or repair process undertaken by the company. With the existence of the problem, the writer wanted to audit the existing governance in companies that have problems regarding aspects of information technology delivery. The author uses the COBIT 5 framework on the DSS domain (Deliver, Service, and Support) and focuses on the sub domains of DSS01 Manage Operations, DSS02 Manage Service Requests and Incidents, DSS03 Manage Problems, and DSS06 Manage Business Process Controls. The assessment method used is a capability model consisting of five capability levels. Based on the audit of information technology governance conducted by researchers using COBIT 5, then the conclusion of this study is the average capability level of the overall process obtained most of the process has reached level 1 performed process.